Direct effects of humic substances on organisms - Bittner, Michal (2006)
Humic substances (HS) are ubiquitous in the environment. However, some studies indicate that HS could induce direct adverse effects on human health and hormone-like effects in fish, amphibians and invertebrates. In this work we investigated a possible biochemical mechanism of HS toxicity via activation of the aryl hydrocarbon receptor (AhR). AhR mediates the toxic and biological effects of environmental contaminants such as 2,3,7,8 tetrachlorodibenzo-p-dioxin, but a number of structurally diverse compounds has also been found to activate AhR. Our results indicate that also humic acids or their fragments can elicit significant inductions of AhR mediated effects in vitro.